Diversification of ortho‐Fused Cycloocta‐2, 5‐dien‐1‐one Cores and Eight‐ to Six‐Ring Conversion by σ Bond C−C Cleavage. Issue 35 (25th July 2016) - Eccleshare, Lee; Lozada‐Rodríguez, Leticia; Cooper, Phillippa; Burroughs, Laurence; Ritchie, John; Lewis, William; Woodward, Simon
Abstract: Sequential treatment of 2‐C6 H4 Br(CHO) with LiC≡CR 1 (R 1 =SiMe3, t Bu), n BuLi, CuBr⋅SMe2 and HC≡CCHClR 2 [R 2 =Ph, 4‐CF3 Ph, 3‐CNPh, 4‐(MeO2 C)Ph] at −50 °C leads to formation of an intermediate carbanion ( Z )‐1, 2‐C6 H4 CA (=O)C≡CB R 1 CH=CH(CH − )R 2 (4 ). Low temperatures (−50 °C) favour attack at CB leading to kinetic formation of 6, 8‐bicycles containing non‐classical C ‐carbanion enolates (5 ). Higher temperatures (−10 °C to ambient) and electron‐deficient R 2 favour retro σ‐bond C−C cleavage regenerating4, which subsequently closes on CA providing 6, 6‐bicyclic alkoxides (6 ). Computational modelling (CBS‐QB3) indicated that both pathways are viable and of similar energies. Reaction of6 with H + gave 1, 2‐dihydronaphthalen‐1‐ols, or under dehydrating conditions, 2‐aryl‐1‐alkynylnaphthlenes. Enolates5 react in situ with: H2 O, D2 O, I2, allylbromide, S2 Me2, CO2 and lead to the expectedC ‐E derivatives (E=H, D, I, allyl, SMe, CO2 H) in 49–64 % yield directly from intermediate5 . The parents (E=H; R 1 =SiMe3, t Bu; R 2 =Ph) are versatile starting materials for NaBH4 and Grignard C=O additions, desilylation (when R 1 =SiMe) and oxime formation. The latter allows formation of 6, 9‐bicyclics via Beckmann rearrangement. The 6, 8‐ring iodides are suitable Suzuki precursors for Pd‐catalysed C−C coupling (81–87 %), whereas the carboxylic acids readily form amides under T3P® conditions (71–95 %). Abstract : Medium‐ring compounds : Simple 1–3 step processes provide access to 6, n ‐bicyclic ring systems ( n =6, 8, 9) and other rapidly prepared derivatives (see scheme). Several of the compounds described herein have already revealed significant activity in open‐innovation drug‐discovery programmes.